EVALUATION OF THE EFFECTIVENESS OF FREE NICOTINE PATCH THERAPY IN A CHARITY CLINIC FOR SMOKING CESSATION - SYED WAJID ALI; Sultan Alghadeer Alghadeer; Mohammed N Alarifi; Salmeen D Babelghaith (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2016)
The purpose of this study was to evaluate the efficacy of a free nicotine- patch therapy for smoking cessation in Saudi smokers. A single centered prospective study was carried out in a charity clinic for smoking cessation in Riyadh, Saudi Arabia. A total of 31 subjects who attended the smoking cessation clinic from June 2014 to August 2014 were studied. All participants were male and their mean age was 31.1±6.4 years. The duration of history of smoking was 12.9±6.8 years. The nicotine- patch therapy outcomes were measured at baseline and at 6 weeks after using nicotine- patch therapy. At base line the number of cigarettes per day was 27±10 and carbon monoxide (CO) level was 20.2±8.3. The analyzed statistics revealed that there were significant decreased in the number of cigarette per day (p=0.001) and Carbon Monoxide (CO) level (p=0.001) over 6 weeks of nicotine- patch therapy. After 6 weeks of therapy, abstinence rate was 58 % (verified by CO level) and no serious adverse reactions were documented. The most common side effects were nausea, headache and local irritation sings. In addition, our finding revealed that smokers were likely to suffer from withdrawal symptoms following trying to quit. These withdrawal symptoms include sleep disturbance, loss of concentration and weight gain as well as irritability. Results of this study show that free nicotine-patch therapy is an effective measure for smoking cessation in Saudi population.Keywords: nicotine patch therapy, smoking cessation clinic, side effects